Exploring the sustainability dimension to position Portuguese Beiras region endogenous resources as green products in the global market - Soares Julião, Jorge Manuel; Calvete Gaspar, Marcelo Rudolfo; Tjahjono, Benny (Instituto Politécnico de Castelo Branco (IPCB), 2016)
Regional endogenous products are commonly perceived by consumers as cultural commodities. In a global market, where culturally differentiated products are difficult to shift due to the lack of awareness of their associated benefits, regional endogenous products are less appealing to consumers than mass-branded goods. As a consequence, regional products are mainly acquired by local consumers, narrowing the potential market to those who are mainly interested in regionally differentiated goods. A paradigm change related to endogenous resource products must be developed to widespread their market to a global scale, promoting a larger consumer-base and consequently enhancing local dynamics and competitive positioning of the regional ecosystems where such goods are produced. The purpose of this study is to explore the sustainability characteristics of endogenous products associated to the Portuguese Beiras Region and their role as a differentiation claim to a global mass-market. In-depth interviews were conducted with local Academia researchers and decision makers in order to explore the benefits of leveraging the sustainability dimension of local produced goods and forecast their effect on a global mass-market. Preliminary findings allowed inferring about the significance of the proposed green claim, but a gap was identified regarding the lack of information to customers regarding the associated distinctive attributes. Further research is needed to assess the remaining multiple-helix actors of the local ecosystem on identifying and developing the most promising strategies to effectively promote local endogenous produce to a global market.
Published by Instituto Politécnico de Castelo Branco (IPCB). This is the Author Accepted Manuscript. This article may be used for personal use only. Please refer to any applicable publisher terms of use.
Keywords: regional ecosystems; endogenous resources; eco-innovation; green products; sustainability